Kenya : Can the Private Sector Help Train Youth for Jobs? - World Bank (Washington, DC, 2017)
The World Bank is committed to working with governments to give everyone the ability to lead productive and healthy lives and getting youth ready for and in jobs is part of this. In Kenya, the World Bank supported a pilot program to give unemployed youth access to job training and private sector internships. An impact evaluation found that those who went through the program were more likely to end up with paid employment, and that young women in particular were also more likely to open a bank account and save money. The Government of Kenya and the World Bank are using the results to help expand the program to reach more young people and give them the opportunity to learn skills and find jobs. Finding effective ways to help unemployed and underemployed youth make the transition from low-paid informal labor to higher paid wage labor is a major challenge for policymakers across the globe. The results from this study contribute to a growing body of evidence on the role that training programs can play in addressing this challenge. The findings suggest that offering young people training and work experience in the private sector is a promising way to put youth in jobs and increase their earnings in urban settings throughout Africa. In addition to increasing employment, the program encouraged youth to participate in more skills training and internships, and got more young people to open bank accounts and use them. The results mirror other similar findings from different countries in Latin America, suggesting private sector training and internships, provided in collaboration with governments, are a promising way to increase youth opportunity in a range of settings.